Legal study on concept of hibah (gift) of faraid shariah law in Malaysia: property management (harta pusaka) on land matters and money / Izzan Farah Hanim Che Husain ... [et al.] - Che Husain, Izzan Farah Hanim; Mohd Isa, Nur Alia; Mohamed Raimi, Siti Fatimah; Sd Abd Jamal, Sharifah Attahiyah (2013)
This research is carried out in order to propose the incorporation of hibah law as an aid to faraid system. There are issues concerning property management among muslim in Malaysia that are left unsettle and unresolved. Hence, to fix these problems it is essential to incorporate hibah law as an aid to faraid system. The method used in this research is the qualitative method. References are done to Statute, Journal, and Article from the reliable internet materials. Interviewed were also conducted with academician and officer from well-known institution that conducted hibah from the social and legal perspective. The academician and the officer were Encik Indere Sharil bin Mohd Shahid, Encik Mohammad Mahyuddin bin Khalid, Encik Safrul Kamalizam and Zainah bt Md Isa. The goal for this research to show that hibah is more effective and encouraged for property management among society and to promote this law. This research will also show study that procedure of hibah is possible and easy to be done. The education to the people is also important to avoid further misinterpretation.